PENGGUNAAN POP UP BOOK UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI KELAS IV SDN 1 SLEMPIT - Nanang Khoirul Umam; Hardian Iskandar; Afakhrul Masub Bakhtiar (JUSEDA, 2020)
This study attempts to increase skill described writing poetry use Pop Up Book in fourth grade students SDN 1 slempit a year 2019/ 2020. It is the type of research the act of a class by research Arikunto design used model consisting of 4 first is planning, do, observation, and reflection. Subject of study there are 19 students. Technique used the test data collection and an instrument used the sheets test writing poetry to know increase skill writing poetry. Based on the results of the analysis done by researchers, increase skill or writing reached percentage of classical of 80,79 % or complete all students in learning writing poetry.